Pelatihan Pemanfaatan Limbah Pertanian Sebagai Pupuk Dan Mulsa Organik Bagi Kelompok Tani Harapan Desa Slateng Ledokombo Menuju Zero Waste - Basuki; Vega Sari; Ahmad Ilham Tanzil (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Jember is part of ​​East Java with 65% of the area dominated by agriculture. Agricultural waste produced from various crop commodities in each region has a large amount of biomass. Hope farmer groups located in the Ledokombo area, precisely in Slateng Village, have a group of 25-30 members with an area of ​​15-30 hectares. The potential for waste generated from each crop commodity in farmer groups is expected to be abundant after each harvest and most of it is not utilized properly and is sometimes spread by the side of the road. The aim of the service program is to provide counseling and training on the use of agricultural waste as organic fertilizer and mulch. Community service activities were carried out in the Hope Farmers' Group, Slateng Village, Ledokombo District, Jember Regency from July to August 2022. Service activities were carried out through several methods, namely counseling/socialization, and training. Among 85% of participants were very satisfied and 15% satisfied with the material presented and 90% of the participants supported about the sustainability of the program and could carry out training activities with different programs.